FACTORS INFLUENCING THE INITIAL PUBLIC OFFERING OF INDONESIAN MANUFACTURING COMPANIES - Fenty Fauziah (Sean Institute, 2023)
This research aims to analyze and explain factors influencing the initial public offering of Indonesian manufacturing companies. The object of this research is manufacturing companies listed on the Indonesia Stock Exchange for the 2019 period. The population of this research is all companies manufacture which is listed on the Indonesian Stock Exchange, with an observation period starting in 2019. The sample selection in this study used a purposive sampling method. Data analysis and hypothesis testing were carried out using a structural equation modeling approach using the eviews 11. The results of the study showed that there was a significant influence on the variables used in the research except inflation, as well as companies listed on the stock exchange as public companies in making the decision to conduct an IPO for consider all factors